A migrating corrosion inhibitor evaluated in concrete containing various contents of admixed chlorides - Morris, W. (2002)
The performance of a surface-applied migrating corrosion inhibitor (MCI) based on an alkylaminoalcohol was evaluated on concrete specimens containing reinforcing steel bar (rebar) segments. Two water/cement ratios (w/c's), various chloride contents and two exposure conditions were investigated. The inhibiting efficiency was followed over a period of 1000 days by means of parameters such as corrosion potential, corrosion current and electrical resistance. Results show that when concrete is exposed to the marine environment, the inhibitor is able to reduce the corrosion rate (CR) only when the initial chloride content is below 0.16 wt.% relative to cement content. Efficiency increases as the w/c increases. There is no beneficial effect when the initial chloride content is greater than 0.43%. When concrete is immersed in a saline solution, no beneficial effect associated to the use of the inhibitor could be appreciated, regardless of w/c or initial chloride content in concrete.